An Extension of the Bollinger Scoring System to Analyse the Distribution of Macrovascular Disease of the Lower Limb in Diabetes. (February 2021) - Lowry, Danielle; Vitalis, Antonios; Al Shakarchi, Julien; Psarros, Vasilios; Karkhanis, Salil; Saeed, Mujahid; Narendran, Parth; Tiwari, Alok
Abstract : Objective: While it is generally considered that patients with diabetes mellitus (DM) have more distal peripheral arterial disease (PAD), there is little information on how individual vessels are affected. The aim of this study was to adapt Bollinger's scoring system for lower limb angiograms (DSAs) to include the distal and planter vessels. The reliability of this extension was tested and was used to compare the distribution of disease in two cohorts of patients with and without DM. Methods: Patients who had undergone DSA ± angioplasty for PAD at a single centre between September 2010 and April 2014 were identified. Twenty-five patients' images were reviewed by four clinicians and scored using an extended version of the Bollinger score. A total of 153 patients with DM were matched, for age, sex, ethnicity, smoking, and hypertension, with 153 patients without DM. The infrainguinal vessels were divided into 16 arterial segments, including plantar vessels, and scored using the Bollinger score. The score ranges from 0 to 15. Fifteen represents an arterial segment with more than 50% of its length occluded. Interobserver reliability was tested using interclass correlation (ICC) and Cohen's kappa coefficient. Results: The ICC demonstrated good agreement between observers (0.76 [0.72–0.79]) with good internal consistency (Cronbach's alpha 0.93). When the Bollinger scores were categorised, the results were weaker, Cohen's kappa ranged from 0.39 (standard error 0.033) to 0.54 (0.030). Patients with DM had a higher burden of disease in the anterior tibial and posterior tibial arteries with relative sparing of the peroneal artery and no difference in the plantar vessels. Conclusion: It has been demonstrated that the Bollinger score can be extended to include the distal vessels. This amended scoring system can be used to compare the burden of distal disease in patients with PAD. How the score relates to clinical presentation and outcomes needs further investigation.